Change in quality of life in patients with acromegaly after treatment with octreotide LAR: first application of AcroQoL in Korea. Issue 6 (10th June 2015) - Chin, Sang Ouk; Chung, Choon Hee; Chung, Yoon-Sok; Kim, Byung-Joon; Kim, Hee Young; Kim, In-Ju; Kim, Jung Guk; Kim, Min-Seon; Kim, Seong-Yeon; Lee, Eun Jig; Lee, Ki Young; Kim, Sung-Woon
Abstract : Objectives: This study was designed to investigate changes in health-related quality of life (HRQoL) of patients with acromegaly in Korea after medical treatment with octreotide LAR using the validated Korean version of the acromegaly quality of life questionnaire (AcroQoL). Design: A prospective, open-label, single-arm study. Setting: 11 tertiary centres in Korea. Participants: 58 Korean patients (aged 21–72 years) who were newly diagnosed with acromegaly between 2009 and 2012 were prescribed octreotide LAR 20 mg at the time of enrolment. During 24 weeks of observation, AcroQoL survey questionnaires and measurement of growth hormone insulin-like growth factor 1(GH/IGF-I) were performed at baseline, week 12 and week 24. Main outcome measures: We assessed the HRQoL of Korean patients with acromegaly after medical treatment with octreotide LAR using the validated Korean version of the AcroQoL questionnaire. Results: Patients had a mean age of 47.2 years (29 males), and GH and IGF-I significantly decreased during the first 12 weeks (GH: 4.8 vs 1.9 μg/L, p<0.001; IGF-I: 497 vs 265 μg/L, p<0.001), but showed insignificant change at week 24 (GH: 2.3 μg/L; IGF-I: 294 μg/L). Only AcroQoL scores for the psychological appearance subdomain showed a significant increase during the entire 24 weeks (p<0.05). The change in the psychological appearance subdomain of AcroQoL scores demonstrated a significant but weak negative correlation with change in IGF-I levels (r=−0.282, p=0.039). When patients were divided into two groups according to their disease activity at week 24 (controlled vs uncontrolled), there was no difference in AcroQoL scores, but the psychological appearance subdomain of the two groups appeared to change differently over the entire 24-week period (p=0.047). Conclusions: Medical treatment with octreotide LAR in patients with acromegaly has a limited contribution to HRQoL as assessed by the AcroQoL.